Complications associated with cutaneous aesthetic procedures. (14th July 2015) - Hartmann, Daniela; Ruzicka, Thomas; Gauglitz, Gerd G.
Summary In recent years, a plethora of novel therapeutic approaches to fight signs of aging and to influence external body appearance have become available in aesthetic dermatology. Extensive research in this field has led to advanced understanding of the anatomy and physiology of the aging face. To successfully address the complex age‐related alterations anti‐aging treatment nowadays calls for a multi‐faceted approach. Most frequently utilized aesthetic procedures include the use of botulinum toxin, a variety of filling substances, microneedling (collagen induction therapy), chemical peeling, lasers, radiofrequency, thread facelift and injectional lipolysis with phosphatidylcholine/deoxycholate among others. Unfortunately, many clinicians still lack in‐depth understanding of potential complications, risk factors and side effects associated with minimal‐invasive procedures. The following review aims to give a broad overview of nowadays most frequently used approaches in the dermato‐aesthetic field and their related complications.